Ion-selective electrodes - Koryta, Jiří.; Štulík, Karel. (Cambridge University Press, 2009)
In this edition, a compact and unified treatment of the theory of ion-selective electrodes is presented along with an updated account of their analytical, biomedical and physicochemical applications.
Previous ed.: 1983
Includes bibliographical references and index.
In this edition, a compact and unified treatment of the theory of ion-selective electrodes is presented along with an updated account of their analytical, biomedical and physicochemical applications.
Keywords: Electrodes, Ion selective. / http://id.loc.gov/authorities/subjects/sh85042120